2008
DOI: 10.1074/jbc.m801359200
|View full text |Cite
|
Sign up to set email alerts
|

Prostaglandin E2 Attenuates Preoptic Expression of GABAA Receptors via EP3 Receptors

Abstract: Prostaglandin E 2 (PGE 2 ) has been shown to produce fever by acting on EP3 receptors within the preoptic area of the brain. However, there is little information about the molecular events downstream of EP3 activation in preoptic neurons. As a first step toward this issue, we examined PGE 2 -induced gene expression changes at single-cell resolution in preoptic neurons expressing EP3. Brain sections of the preoptic area from PGE 2 -or saline-injected rats were stained with an anti-EP3 antibody, and the cell bod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
1

Year Published

2008
2008
2015
2015

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 31 publications
1
14
1
Order By: Relevance
“…The preoptic region of the anterior hypothalamus was shown to mediate the fever response and to participate to the HPA-activation (Saper et al, 2012;Ulrich-Lai and Herman, 2009) and hyperalgesia (Abe et al, 2001). Despite a high representation of EPs in this region we could not identify any of the inflammation-induced gene expression changes to be regulated by PGE2 (paper IV), which seems to be in line with the sparse evidence in the literature (Tsuchiya et al, 2008), and which suggests that most of the effects of PGE2 are nontranscriptional.…”
Section: Brain Pge2 As a Mediator Of Fever At The Preoptic Regionsupporting
confidence: 77%
See 2 more Smart Citations
“…The preoptic region of the anterior hypothalamus was shown to mediate the fever response and to participate to the HPA-activation (Saper et al, 2012;Ulrich-Lai and Herman, 2009) and hyperalgesia (Abe et al, 2001). Despite a high representation of EPs in this region we could not identify any of the inflammation-induced gene expression changes to be regulated by PGE2 (paper IV), which seems to be in line with the sparse evidence in the literature (Tsuchiya et al, 2008), and which suggests that most of the effects of PGE2 are nontranscriptional.…”
Section: Brain Pge2 As a Mediator Of Fever At The Preoptic Regionsupporting
confidence: 77%
“…Nonetheless, even in that model, in which the gene regulatory effects were examined briefly after icv injection of PGE2, few genes were identified that were changed by the stimulus, and these genes generally displayed low fold changes (between 1.5 and 2). However, in that study (Tsuchiya et al, 2008) it was reported that the GABAA transcript was attenuated by PGE2, a finding that could not be verified in our present work.…”
Section: Discussioncontrasting
confidence: 56%
See 1 more Smart Citation
“…The preoptic area expresses EP 3 receptors that provide direct pyrogenic input to two hyperpyrexia generating sympathoexcitatory brain regions, the dorsomedial hypothalamus (Nakamura et al, 2005), and the rostral raphe pallidus nucleus (Nakamura et al, 2009). It has been suggested that EP 3 receptors cause a decrease in preoptic GABA A expression as a mechanism for PGE 2 -induced fever (Tsuchiya et al, 2008).…”
Section: Distribution and Biological Functionsmentioning
confidence: 99%
“…LPS-induced febrile response is blunted in mice deficient in mPGES-1 as well as those deficient in COX-2 or the PGE receptor EP3 [13,39,86]. Cerebral vascular endothelial cells express COX-2 and mPGES-1 enabling pro-inflammatory cytokines to stimulate the synthesis of PGE 2 , whose small size and lipophilic property allow it to pass across the blood-brain barrier into CNS neurons, where the PGE 2 /EP3 signaling elicits G i/o activation in preoptic thermocenter neurons by decreasing preoptic GABA type a receptor expression [84]. mPGES-1 expression is induced in neurons, microglia, and endothelial cells in the cerebral cortex after transient focal ischemia.…”
Section: Pain Fever and Nerve Injurymentioning
confidence: 99%